Immersive Virtual Environment as an Educational Resource: A Learning Tool for Data Structures and Algorithms - Soussa, Márcio; Brito, Gabriel de; Alberto, Carlos; Henrique, Pedro; Costa, Tiago; Thasla, Yasmim; Ebert, Sanval; Lima, Claudia; Winkler, Ingrid (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais Estendidos do XXVII Simpósio de Realidade Virtual e AumentadaDO - 10.5753/svr_estendido.2025.15696, 2025)
The abstract nature of data structures and algorithms (DSA) remains a challenge in computer science education. This study introduces an educational tool using virtual reality and metaverse technologies to support DSA teaching and learning. Following a Design Science Research approach, we developed two versions: a VR environment and a metaverse platform. Forty students evaluated didactic effectiveness and usability, while eight assessed usability and immersion. Results showed significant gains in conceptual understanding (p < 0.05), especially for stacks and queues. Usability scores were strong (80 and 75.3), but the Igroup Presence Questionnaire score of 2.92 revealed limited immersion, potentially affecting engagement. These findings suggest the tool effectively supports conceptual learning but requires refinements in interactivity to enhance immersion and practical problem-solving. Future work will expand content coverage and address immersion gaps to consolidate its contribution to virtual learning environments.